Ideology studies - Freeden, Michael, author.
1 online resource
Keywords: "This book comprehensively collects the thinking - over the last 25 years - of one [of] the most important contemporary scholars in the field of ideology studies. Clearly organised, it expounds on the changing nature of the sub-discipline, its components and methods of investigation. As such, it serves the need for a general, well-informed identification and elaboration of thematic possibilities in current ideology studies and represents the most developed and productive methodological approach to the study of ideologies in the last three decades. Freeden presents ideology studies as an evolving and vibrant field, encountering and surmounting a series of challenges in its successful path towards recognition as a fully legitimate and respected branch of political theory. This book will be of key interest to students and scholars of political ideologies, political theory, political philosophy and more broadly to sociology, political science, anthropology, human geography, international studies, and the humanities"--